Analisis Kemampuan Visual-Spasial Dalam Menyelesaikan Masalah Geometri Ditinjau Dari Gaya Belajar Siswa Kelas X SMK Yadika 8 Jati Mulya - Ema Lestari; Sintraka Kesumat Wargani; Friska Agustina Silaban (Pusat Riset dan Inovasi Nasional, 2023)
Based on preliminary study data at Yadika 8 Jatimulya Vocational School, it was found that mathematics scores, especially in understanding and solving geometric problems, were still low. This information was obtained through documentation studies and interviews with mathematics teachers in class X majoring in AKL-1, who revealed students' difficulties in understanding and solving geometry problems. Even after the material and examples have been taught, students still experience difficulties when faced with new questions with changes in numbers and question patterns. Their ability to analyze story problems and picture questions and relate them to objects around them is also relatively low. In response to these findings, this research aims to describe the spatial abilities of students who have visual, auditory and kinesthetic learning styles. This research is entitled